Genrers rörlighet: Genredefinitionens dilemma sett i ett semantiskt perspektiv - Hættner Aurelius, Eva (Tidskrift för litteraturvetenskap, 2014)
The Mobility of Genres. The Dilemma of Genre Definition, a Semantic Perspective Fundamentally there are two major ways of defining a (literary) genre. If genres are conceived of as logical classes, the definition is subjected to the demands of class-definitions, in order to function as terms in scientific discourse. However, if genres are conceived of as cultural or social conventions, the definition has another logical character. The genres of the first type are referred to as theoretical genres, the genres of the second type, historical genres. This article describes a number of problems associated with the first theory, for example, their lack of hermeneutical value, since they per definition are not text-inherent. The historical genre, by contrast, allows for a certain vagueness on the part of definition. This article also considers the logical problem of falsification and verification of the theoretical genres.The distinction natural language and meta-language is evoked, to indicate the fact that natural languages are constantly defying this distinction. How then to define these genre-terms, if they belong to a natural language? The fundamental dualistic character (res–verba, sign–concept, word–meaning, etc.) of the realistic semantic is described, as is its problematic nature in the enterprise of defining types. The pragmatic semantic offers a solution for this problem, conceiving of meaning as something existing in the use of language, not as anything outside of use, and thus avoiding the dualism of the realistic semantic. The use is rule-governed, and an utterance is an element in a language-game, subject to rules. The logical consequence of this, is that a definition must be contextually fixed. Thus, if the genre-terms: 1) belong to the ordinary language and not only to the language of science, and 2) if the purpose is to describe the rules governing the use, then the only possible conclusion concerning this task, is to fix language-use within the space and the time dealt with by the investigation. This may result in a certain vagueness of definition, but the gain is the acquiescence of great hermeneutical value, since the genre, conceived of in this way, exists both inside and outside the text, thus incorporating not only textual meaning, but also cultural, social or ideological meaning.